PENGARUH TEKNIK EFFLEURAGE, CURCUMA LONGA LINN & TAMARINDUS INDICA TERHADAP DISMENOREA PADA MAHASISWI FAKULTAS ILMU KEPERAWATAN UNISSULA - Rohmania, Widya Lailatur; Distinarista, Hernandia; Rahayu, Tutik (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Background: Dysmenorrhea or menstruation is problem among many women, especially students. Therefore, non-pharmacological techniques are needed to reduce these problems.Objective: This study aim to effectiveness of efleurage massage and herbal drinks Curcuma Longa Linn and Tamarindus Indica in reducing menstrual pain among female students of Sultan Agung Islamic UniversityMethods: The research method uses quantitative nature with case studies, data collection using questionnaires and experimental tests. The number of respondents was 32 people with purposive sampling techniques, sample placement was selected based on inclusion and exclusion criteria that had been set in accordance with the objectives of the studyResults: The results obtained if most respondents (37.5%) experienced moderate menstrual pain, while only 9.4% reported severe pain, highlighting the significant prevalence of dysmenorrhea among female students. Based on the Wiloxcon p value test, the Mann-Whitney test results showed a p-value of 0.013 (p <0.05), which indicated a difference in the level of menstrual pain between the control group using the hegemony group after being given the interventionConclusion: There is an influence of the effluent technique and the administration of curcuma longa linn - tamarimdus indica drink on menstrual pain before and after therapy.